Murine-related helminthiasis: a public health concern at solid waste sites around forest- adjacent communities in Thailand - Nattapon Maneepairoj; Paisin Lekcharoen; Kittipong Chaisiri; Supaphen Sripiboon (Frontiers in Veterinary Science)
Murine-related helminthiasis is a frequently overlooked zoonotic disease with significant public health implications. The role of murine rodents in transmitting these infections to other animals remains under-researched. This study aimed to investigate murine-related helminth infections at solid waste sites, particularly in forest-adjacent communities where murine rodent populations are high and multi-host interactions are possible. During a 5-day trapping session, 36 live traps were deployed across different habitats during both wet and dry seasons. Trapped murine rodents and their gastrointestinal (GI) parasites were morphologically evaluated for species identification. The results revealed that a total of 380 murine rodents were captured, with an overall GI helminth infection prevalence of 86.8% (330/380). The adult male murine rodents exhibited higher prevalence, abundance, and species richness of helminths compared to juvenile and female murine rodents. A total of 16 helminth species were identified, with Trichostrongylus morphotype A showing the highest infection prevalence (53.2%). Six zoonotic species were also detected, including Syphacia obvelata (22.4%), Syphacia muris (12.4%), Raillietina spp. (10.8%), Hymenolepis diminuta (10.3%), Vampirolepis nana (10%), and Cyclodontostomum purvisi (2.4%). Increased population of murine rodents was observed at the solid waste sites, as indicated by higher trap success (TS) rates. Forest murine rodents exhibited a significant prevalence of helminth infections and high species diversity. These findings suggest that solid waste sites adjacent to forests may pose a heightened risk for disease transmission, warranting further attention.